A Note on Discrete Multitime Recurrences of Samuelson-Hicks Type - Bruno Antonio Pansera; Francesco Strati (Discrete Dynamics in Nature and Society)
By this work, we aim at fostering further research on the applications of multitime recurrences. In particular, we shall apply this method by generalizing the Samuelson-Hicks model so as to make the new concept of time that this method proposes clear. In particular, the multitime approach decomposes a point of time into a vector, taking into account how different coordinates of time referring to the same date can affect the dynamics of a model.